The Influence Of Education And Public Awareness On The Use Of Digital-Based Public Services - Indriati Amirullah (International Journal of Social Science and Humanity, 2024)
The rapid advancement of digital technology has transformed how public services are delivered and accessed. This research examines the relationship between education levels and public awareness concerning adopting digital-based public services. In the digital transformation era, understanding the factors that influence the adoption of digital public services is crucial for improving the effectiveness of e-government implementation. This study surveyed 500 respondents from various demographic groups across multiple regions through a quantitative approach, utilizing stratified random sampling to ensure representation. The research employed a structured questionnaire and analyzed the data using multiple regression analysis and Structural Equation Modeling (SEM). The findings reveal a significant positive correlation (r = 0.76, p < 0.001) between educational background and digital service adoption rates. Additionally, public awareness emerged as a crucial mediating factor, explaining 45% of the variance in digital service utilization patterns. The study also identified key barriers to adoption, including digital literacy gaps and accessibility challenges, particularly among lower education groups. These findings provide valuable insights for policymakers and public service administrators in developing targeted strategies to enhance digital service adoption. The research contributes to the growing body of literature on e-government implementation and digital transformation in public services, while offering practical recommendations for improving public service delivery in the digital age.